MiRNA-21 promotes renal carcinoma cell invasion in a microfluidic device. Issue 70 (12th September 2017) - Wang, Xiaogang; Jin, Yiying; Wang, Wei; Yu, Na; Xiao, Xue; Liu, Tingjiao; Li, Xiancheng
Abstract : MicroRNAs (miR) play important roles in cancer invasion. Abstract : MicroRNAs (miR) play important roles in cancer invasion. In this study, we investigated the role of miR-21 in the invasion of renal cell carcinoma. The invasive abilities of renal carcinoma cell lines (786-O, Caki-1, A498), one normal epithelial kidney cell line (HK-2) and primary renal carcinoma cells were assessed in a microfluidic model. The expression of miR-21 was examined by quantitative real time PCR (qRT-PCR). We found that HK-2 cells with low miR-21 expression showed low invasive ability while renal carcinoma cell lines with high miR-21 expression showed high invasive ability. Primary renal cancer cells showed higher invasive ability than HK-2 cells, and this was consistent with the level of miR-21 expression. miR-21 knockdown reduced both renal carcinoma cell line and primary cancer cell invasion. Overall, this study shows that miR-21 promotes renal cancer cell invasion in both cell lines and primary cancer cells and suggests that miR-21 might be a new target in renal cancer therapy. In addition, we demonstrate that a microfluidic device provides a useful in vitro platform to study cancer cell invasion.